Fournier Gangrene in Men and Women: Appearance on CT, Ultrasound, and MRI and What the Surgeon Wants to Know. Issue 1 (February 2020) - Ballard, David H.; Mazaheri, Parisa; Raptis, Constantine A.; Lubner, Meghan G.; Menias, Christine O.; Pickhardt, Perry J.; Mellnick, Vincent M.
Fournier gangrene (FG) is a genitourinary necrotizing fasciitis that can be lethal if not promptly diagnosed and surgically debrided. The diagnosis is often made by physical examination paired with an appropriate clinical suspicion and supporting laboratory values. Imaging, particularly computed tomography (CT), plays a role in delineating involved fascial planes for operative debridement and occasionally in diagnosing FG. Less commonly, the imaging manifestations of FG may also be seen on ultrasound, radiographs, and magnetic resonance imaging. With the ubiquitous use and availability of CT, radiologists have a growing role in recognizing FG. This can be challenging in the absence of fascial gas, but a CT scoring system for necrotizing fasciitis can be helpful in making the diagnosis. Recent series suggest that this predominantly male disease has a rising incidence in women. Women with FG are more likely to be morbidly obese and have vulvar or labial involvement compared to men. Imaging mimics include ulcerative and necrotic tumors, traumatic or iatrogenic fascial gas, and vaginitis emphysematosa. The purpose of this pictorial review is to illustrate the imaging manifestations of FG and its mimics, with emphases on necrotizing fasciitis CT scoring systems and FG in women.